Penghindaran Pajak Sektor Makanan Dan Minuman Di Indonesia : Profitabilitas, Likuiditas Dan Leverage - Purba, Pebisitona Mesajaya; Marjuniarti, Febby; Samosir, Harun Dongan; Sumiok, Cristofer (Politeknik Raflesia Press, 2024)
The purpose of this study is to examine the effect of profitability, liquidity, and leverage on tax avoidance, with capital intensity and inventory intensity as control variables. The type of data used in this study is secondary data, which was obtained from financial statements and annual reports available on the Indonesia Stock Exchange website from 2020 to 2023. The sampling method used is purposive sampling, resulting in a sample of 101 companies over the four-year period. The results of this study indicate that profitability has a negative effect on tax avoidance, while liquidity has no effect on tax avoidance. In contrast, leverage has a positive effect on tax avoidance. Additionally, the variables capital intensity and inventory intensity are able to strengthen the independence of tax avoidance.